NOTCH1 mutation, TP53 alteration and myeloid antigen expression predict outcome heterogeneity in children with first relapse of T-cell acute lymphoblastic leukemia - Hof, Jana; Kox, Corinne; Bandapalli, Obul Reddy; Kunz, Joachim; Muckenthaler, Martina; Kulozik, Andreas (Haematologica, 2017)
Relapse of T-cell acute lymphoblastic leukemia (T-ALL) has a dismal prognosis, with only 20% of afflicted children surviving. Children with relapsed T-ALL are commonly treated within high-risk arms of second-line treatment protocols that include mandatory hematopoietic stem cell transplantation (HSCT) if a second complete remission can be induced.